Modifikasi tepung gadung (Dioscorea hispida Dennst.) dengan fermentasi ragi tape dan annealing serta aplikasinya pada pembuatan cookies - Sri Wahyuni; Andi Khaeruni; Asnani Asnani; Sarinah Sarinah; Andi Dahlan; Asca Rahayu; Erlisa Salim (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
The purpose of this study was to determine the modification of gadung flour, fermented by tape yeast and annealing on the physicochemical and organoleptic characteristics of gadung flour, the quality characteristics of gadung flour, and the taste of cookies. This study used a completely randomized design (CRD), namely modified annealing at 50°C for 16 hours (A5.16), yeast fermenting tape with a concentration of 6% for 12 hours (F6.12), and a combination of yeast tape and annealing (AK). Analysis of the viscosity, swelling power, and solubility were observed variables. The result showed that the values of viscosity, swelling power, solubility, and HCN were 18.75 cP, 14.28 g/g, 14.13%, and 13.85 mg/kg, respectively. The nutritional value of modified annealed gadung flour, tape yeast fermentation, and sequential tape yeast and annealing combination, encompassing the moisture content of 6.22-6.70% on a dry basis, ash content of 1.80-1.99% on a dry basis, fat content of 3.15-3.82% on a dry basis, protein content of 6.32-7.20% on a dry basis, crude fiber content of 17.12-19.62% on a dry basis, glucose content of 30.54-33.84% on a dry basis, and carbohydrate content of 81.17-82.05% on a dry basis. The nutritional value of modified gadung flour cookies which includes moisture content, ash content, fat content, protein content, crude fiber content, glucose, and carbohydrate content are 7.85% wb, 1.93 ww%, 14.79 ww%, 10.49% db, 12.25% db, 39.12% db, and 69.13% db respectively. The results of the organoleptic assessment of modified gadung flour cookies included color, aroma, texture, and taste were 3.90 (liked), 4.13 (liked), 3.40 (a bit crunchy), and 3.90 (liked). Based on SNI gadung flour and cookies modified gadung flour by tape yeast fermentation and annealing have met the SNI.